Mengintegrasikan Teori Pembelajaran Konstruktivis melalui Teknologi Digital Dalam Pendidikan Islam - Kurniawan, Fajar Fahrozi; Rahmah, Amelia Habibatur; Anbiya, Bakti Fatwa; Zubair, Muhammad (LP2M Universitas Islam Ahmad Dahlan, 2024)
Constructivist theory is a learning theory that emphasizes the active role of students in constructing their own knowledge. This theory continues to be the dominant research program in producing new research and findings. With the development of technology, this theory has also begun to be integrated into digital technology, this integration prompted us to conduct research on this integration. This integration is also applied in Islamic education, so we examine the integration of constructivist theory with digital technology in Islamic education. This study aims to analyze the integration of constructivist learning theory in digital technology Islamic education. This study using library research produces research data regarding the challenges, strategies, benefits and impacts of integrating constructivist learning theory in digital technology Islamic education. This study has implications for increasing literature on Islamic education, a development to incorporate learning theory into technological advances on digital Technology, so that it can add to the body of knowledge in the field of education regarding this integration, especially in Islamic education.